2015
DOI: 10.1016/j.str.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane- and Soluble-Protein Helix-Helix Interactome: Similar Geometry via Different Interactions

Abstract: Summary Alpha-helices are a basic unit of protein secondary structure and therefore the interaction between helices is crucial to understanding tertiary and higher-order folds. Comparing subtle variations in the structural and sequence motifs between membrane and soluble proteins sheds light on the different constraints faced by each environment and elucidates the complex puzzle of membrane protein folding. Here, we demonstrate that membrane and water-soluble helix pairs share a small number of similar folds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 75 publications
(90 reference statements)
5
83
0
Order By: Relevance
“…[1][2][3] Because these small residues do not have sufficient side chain hydrophobicities to compensate for the partitioning of the polar main chain of the helix into membranes, [4] the polar surfaces can preferentially pack with each other to avoid lipid exposure. The impact of small residues on transmembrane helix-helix interactions is likely not only of a passive nature, but also involves active forces, such as van der Waals interactions and C α H⋯O=C hydrogen bonds.…”
mentioning
confidence: 99%
“…[1][2][3] Because these small residues do not have sufficient side chain hydrophobicities to compensate for the partitioning of the polar main chain of the helix into membranes, [4] the polar surfaces can preferentially pack with each other to avoid lipid exposure. The impact of small residues on transmembrane helix-helix interactions is likely not only of a passive nature, but also involves active forces, such as van der Waals interactions and C α H⋯O=C hydrogen bonds.…”
mentioning
confidence: 99%
“…Subsequent analysis based on a much expanded structural database indicated that helical dimer motifs of soluble and membrane proteins share similar geometries, but the membrane motifs are enriched in small amino-acids to facilitate the formation of hydrogen bonds (both side-chain mediated and backbone mediated hydrogen bonds, i.e. Cα–H···O) 22 . This is consistent with the particular importance of hydrogen bonding interactions in establishing tertiary and quaternary structure in membrane proteins 23,24 .…”
Section: Structural Motifs As Membrane Protein Design Building Blocksmentioning
confidence: 99%
“…Several studies have characterized helix-helix associations, showing that they can be described with a small set of structural classes or restricted parameters [23-27]. Grigoryan and Degrado used a generalized set of parameters to describe the structural space of helical bundles [25], showing that coiled coils largely sampled near-ideal parametric structures.…”
Section: Introductionmentioning
confidence: 99%